Thermoplastic Analysis of State Diagrams of Cryoprotective Solutions - Sevastianov, Stanislav; Osetsky, Oleksandr; Gurina, Tetiana (Problems of Cryobiology and Cryomedicine, 2024)
Probl Cryobiol Cryomed 2024; 34(4):297